Penanaman Nilai Toleransi Melalui Pembelajaran PAI di Madrasah - Rizki Aulia; Nurul Ilmianah; Ruslan (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the inculcation of tolerance values through Islamic Religious Education (PAI) learning in madrasahs. The study was motivated by the importance of tolerance in Indonesia’s pluralistic society and the emergence of intolerant attitudes within educational environments. This research employed a qualitative approach using library research methods by reviewing books, scientific journals, articles, and other relevant documents. The collected data were analyzed using content analysis techniques to obtain a comprehensive understanding of the concept and implementation of tolerance values in PAI learning. The findings reveal that tolerance in Islam (tasamuh) includes attitudes of mutual respect, appreciation of differences, non-coercion, and the maintenance of social harmony. PAI learning has a strategic role in instilling tolerance values through the integration of learning materials, interactive teaching methods, teacher role modeling, and the creation of an inclusive school culture. The study implies that strengthening tolerance-based character education through PAI learning can support the development of students who are able to live harmoniously in a diverse society.